New combination of super-twisting and Kalman filter for direct power control of distributed generation at different operations. (July 2019) - Elnady, A.; AlShabi, M.; Adam, A.A.
Highlights: Super twisting technique is innovatively used to control the direct power control. Kalman filter is formulated to estimate the feedback power. Kalman filter is formulated to estimate the feedback voltages. The direct power control is used in a grid-connected mode. The direct power control is used in a stand-alone mode. Abstract: This paper presents an efficient modification of the direct power control scheme employed to precisely control the power of the distributed generation system. This modification is articulated for utilizing the super-twisting technique for controlling the feedforward power and Kalman filter for estimating the feedback power. The combination of the super-twisting technique and Kalman filter for the direct power control achieves a seamless steady-state and dynamic performance for the injected power by the distributed generation system in a grid-connected mode. Furthermore, the concept of direct power control is modified to operate the distributed generation system in a stand-alone mode so as to stabilize the voltage at different loading conditions, where the feedback voltage is estimated by a simple formulation of Kalman filter. The proposed control scheme for the distributed generation system is compared to several control schemes such as the conventional direct power control operated by space vector modulation and another proposed 1st order sliding mode control based direct power scheme. Simulation results are presented to prove the meritorious performance of Kalman filter and the super-twisting technique for the power and voltage control schemes. Experimental results are provided to prove the practicality of the super-twisting technique for the operation of the direct power control in a grid-connected mode.